A rare presentation of anomalous origin of left coronary artery from the pulmonary artery in a young adult - Kumar, Krishna Raja; Mohammed, Fazil Azeem; Russel Starlet, Abisho; Saxena, Prasoon; Satish, Ammapalem (International Journal of Research in Medical Sciences, 2024)
Anomalous origin of left coronary artery from the pulmonary artery (ALCAPA) is a very rare congenital cardiac disorder with an incidence of about 1 in 300000 live births. The majority of patients are symptomatic in early infancy with symptoms of intractable heart failure. Only very few patients survive to adulthood with minimal symptoms. A young female was referred to us in view of breathlessness, clinical examination didn’t show any signs except a grade 2 systolic murmur in the pulmonary area. The patient underwent 2D echocardiography evaluation which revealed suspicion of ALCAPA and was confirmed using coronary angiography. The patient underwent surgical closure of ALCAPA along with left internal mammary artery (LIMA) to left anterior descending (LAD) anastomosis, postoperative period was uneventful, on routine follow-up the patient is doing well with resolution of dyspnea. ALCAPA is a very rare disorder and most of it is diagnosed in infancy and not many surviving beyond infancy, high degree of suspicion of ALCAPA is needed for young patients presenting with symptoms of angina, heart failure.